Evaluation of Quartz Sand Deposit from Abu Dalam Area, Bara Locality, Sudan - IM Abdallsamed, Mohammed; A Elmansour, Asim; A Salih, Mushal; M Ibrahim, Elhadi; A Mustafa, Hassan; A Elhadi, Mohammed; D Mohammed, Ahmed (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2021)
The study area is mainly composed of granitic gneisses, migmatites, quartzites, and schists in some parts. Regional and small scales exploration was carried out in the sand dunes of Abu Dalam El Ama, Bara Locality to find quartz sands occurrences to cover most of the geologically favorable areas. During the field visits, quartz sand samples were collected from 12 points of the area. Ten representative samples were collected from the Abu Dalam area and were tested for their suitability to be used as raw materials for different industrial uses. The suitability of quartz sand deposits from the Abu Dalam area, Bara Locality for commercial glass production were assessed based on the chemical and physical properties. Tests were carried out at the University of Kordofan, Sudan, and the Geological Research Authority of Sudan (GRAS). The chemical analysis was carried using Atomic Absorption Spectroscopy (AAS). The particle size was carried out using a mechanical shaker (sieving method). The quartz sand from the study area had the highest SiO2 content of 91.01%, which were found to be within the acceptable limits for glass making. The percentage of Fe2O3 , MgO, CaO, Al2 O3 Na2O, and K=O in the quartz sand samples were very low and can be suitable industrial glass making. The physical satisfy the standard requirements for glass making. How to cite this article: Abdallsamed MIM, Elmansour AA, Salih MA et al. Evaluation of Quartz Sand Deposit from Abu Dalam Area, Bara Locality, Sudan. J Adv Res Geo Sci Rem Sens 2020; 7(1&2): 1-5.